The Application of DLC Coating on Convex-concave (C-C) Gearings - Gondar, Ernest; Bosansky, Miroslav; Rusnak, Juraj; Toth, Frantisek; Repkova, Jana (Manufacturing Technology Journal, 2019)
This paper discusses the possibility of increasing the surface load capacity in C60E steel gearings by applying DLC thin coating. It describes the effect of tribological characteristics, such as friction coefficient, wear, adhesion and hardness of DLC coating on convex-concave gearing (C-C). The average thickness of DLC coating is 1.2 μm. Delamination of the DLC coating was recorded at a load of approximately 50 N. The friction coefficient of the DLC coating was 0.09. The nano-hardness of the DLC coating was 14.4 GPa. The results of the tests to scuffing on C-C gearings on the Niemann tester show that the DLC coating deposition occurred at load level 5. The complete removal of the coating was preceded by gradual thinning. After its removal, the wear continued substrate, where the traces after milling filled-up with the substrate metal.
Keywords: Convex-concave gearing; DLC; friction coefficient; Niemann's test